Effects of a Participatory Learning Program on the Knowledge and Skills of Practical Roles Among Village Health Volunteers in Pratupa Subdistrict, Muang, Lamphun - langumong, Nongnuch; Wongchum, Rungrudee (Thai Red Cross Nursing Journal, 2023)
The purpose of this quasi - experimental research, with one group pretest - posttest design, was to examine the effects of a participatory learning program on the knowledge and skills of practical roles among village health volunteers in Pratupa sub - district, Muang, Lamphun. Thirty samples were purposively selected to participate in the learning program. The participatory learning program consisted of a pretest (week 1), attending three learning sessions, including Session 1 (sharing experiences and reflecting on the roles of village health volunteers), Session 2 (teaching with demonstration by learning step - by - step with practice following each step), and Session 3 (the conclusion session). The instruments included the participatory learning program and evaluation forms of the village health volunteers’ knowledge and skills of practical roles. The data were analyzed using frequency, percentage, mean, standard deviation, McNemar’s test, Chi - squared test, and one - way repeated measures ANOVA. The results showed that after implementing the program (in weeks 3 and 8), the levels of knowledge were not significantly different, whereas the levels of skills of practical roles were significantly different from those before participating in the program at p < .05. Moreover, the scores of knowledge and skills of practical roles were statistically different from those before participating in the program at p < .001. Therefore, stakeholders should apply the participatory learning program for village health volunteers in order to improve their knowledge and skills of practical roles to increase effectiveness in developing village health volunteers’ capacity to solve the health problems facing communities.